CAMP Imaging at Ryanodine Receptors Reveals β2-Adrenoceptor Driven Arrhythmias. Issue 1 (27th April 2021) - Berisha, Filip; Götz, Konrad R.; Wegener, Jörg W.; Brandenburg, Sören; Subramanian, Hariharan; Molina, Cristina E.; Rüffer, André; Petersen, Johannes; Bernhardt, Alexander; Girdauskas, Evaldas; Jungen, Christiane; Pape, Ulrike; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Rationale: 3′, 5′-cAMP is a ubiquitous second messenger which, upon β-AR (β-adrenergic receptor) stimulation, acts in microdomains to regulate cardiac excitation-contraction coupling by activating phosphorylation of calcium handling proteins. One crucial microdomain is in vicinity of the cardiac RyR2 (ryanodine receptor type 2) which is associated with arrhythmogenic diastolic calcium leak from the sarcoplasmic reticulum often occurring in heart failure. Objective: We sought to establish a real-time live-cell imaging approach capable of directly visualizing cAMP in the vicinity of mouse and human RyR2 and to analyze its pathological changes in failing cardiomyocytes under β-AR stimulation. Methods and Results: We generated a novel targeted fluorescent biosensor Epac1 (exchange protein directly activated by cAMP 1)-JNC (junctin) for RyR2-associated cAMP and expressed it in transgenic mouse hearts as well in human ventricular myocytes using adenoviral gene transfer. In healthy cardiomyocytes, β1 -AR but not β2 -AR stimulation strongly increased local RyR2-associated cAMP levels. However, already in cardiac hypertrophy induced by aortic banding, there was a marked subcellular redistribution of PDEs (phosphodiesterases) 2, 3, and 4, which included a dramatic loss of the local pool of PDE4. This was also accompanied by measurable β2 -AR/AMP signals in the vicinity of RyR2 in failing mouse and human myocytes, increased β2 -AR–dependent RyR2 phosphorylation, sarcoplasmic reticulum calcium leak, and arrhythmia susceptibility. Conclusions: Our new imaging approach could visualize cAMP levels in the direct vicinity of cardiac RyR2. Unexpectedly, in mouse and human failing myocytes, it could uncover functionally relevant local arrhythmogenic β2 -AR/cAMP signals which might be an interesting antiarrhythmic target for heart failure.